Evaluation of value-at-risk models using historical data in Asia. - Lin, Xiuwen. (2008)
The concern of the study is the performance assessment of Value-at-Risk (VaR) models when applied to emerging markets in Asia. The VaR models are assessed on their performances under different parameter settings and under different market conditions. The models investigated include Historical Simulation (HS) and the different volatility models – Simple Moving Average (SMA) and Exponentially Weighted Moving Average (EWMA) under Variance-Covariance (VC). The evaluation is implemented through the use of backtesting, introduced by The Basel Committee on a Banking Supervision in the framework of Basel II. Several potential pitfalls associated with each methodology are highlighted. The results from our empirical study propose that from the regulatory point of view, 99% confidence level is more desired to suffice risk coverage. Small window length is concluded as most favorable when differing weights are not assigned to historical data. Our findings also suggest that HS is the most accurate VaR model which provides adequately for the intended risk coverage. During adverse market conditions, HS may be supplemented with EWMA for better market risk measurement. However, further exploration for the most appropriate model under such conditions should be carried out. Overall, the results presented have important implications for risk managers and market regulators.